Community‐based residential treatment for alcohol and substance use problems: A realist review. (19th July 2021) - Mutschler, Christina; Junaid, Sana; Tellez, Carmina; Franco, Giselle; Gryspeerdt, Charlie; Bushe, Julianne
Abstract: Research and reviews to date suggest that community‐based residential treatments for substance use disorders (SUDs) have mixed effectiveness, with some studies finding positive outcomes while others finding no differences between intervention arms, including inpatient, outpatient, and control groups. In order to understand these mixed findings, reviews have underscored the importance of outlining the active treatment components of residential treatment, as well as treatment mechanisms and outcomes. Further, there is very little research on the underlying theories explaining how and for whom residential treatments are effective. The purpose of the present realist synthesis was to address this gap in the literature by exploring how, why, for whom, and in what circumstances, community‐based residential treatments are effective. Following the RAMESES Publication Standards, a search was undertaken for articles examining community‐based residential treatments in PsycINFO and PubMed from anytime to January 2020. The search generated 28 articles that met inclusion criteria and were extracted for relevant information. Results of the realist synthesis identified six Context‐Mechanism‐Outcome (CMO) configurations. Contextual factors that generated subsequent mechanisms and outcomes included substance‐related problem severity, psychiatric comorbidities, diverse populations, pre‐treatment relationships, lack of structure and lack of coping strategies. These CMO configurations provide important information for clinicians, treatment centres and policy makers, including the specific programme components that need to be offered in treatment to facilitate positive treatment outcomes.